Wearable optical devices and methods of making optical composite materials for such devices

By forming a multi-layer optical composite material using nanoparticles and liquid transfer method prepared by high refractive materials, the problems of low refractive index gradient and limited field of view in the prior art are solved, and the field of view expansion and material stability are achieved.

CN119137512APending Publication Date: 2024-12-13XPANCEO RESEARCH ON NATURAL SCIENCE LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380037394.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-12
Filing Date
2023-07-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When preparing optical materials with high refractive index gradients, the prior art has problems such as material complexity, low refractive index gradient value, insufficient transmittance and limited field of view, making it difficult to achieve expansion higher than the field of view of the human eye.

Method used

Nanoparticles prepared from high refractive materials are prepared by liquid phase femtosecond laser fragmentation or ablation method, and distributed them on optically transparent polymers to form layers with different refractive indices, and superimposed by liquid transfer method. Form a multi-layer optical composite material to achieve high refractive index gradient and wide field of view.

Benefits of technology

The field of view is achieved to exceed the physiological ability of the human eye, up to 325 degrees, and the transmittance and stability of the material are improved, solving the problems of limited field of view and short material life in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137512A_ABST
    Figure CN119137512A_ABST
Patent Text Reader

Abstract

The invention relates to a wearable optical device. The device comprises an optical composite layered polymeric material having Van der Waals nanoparticles having a refractive index higher than 2.8. The difference in refractive index of the layers includes no less than 0.3. The method of preparing such a material comprises: (i) preparing the nanoparticles from a high refractive material using a liquid phase femtosecond laser fragmentation or ablation process; (ii) distributing the nanoparticles on the polymer by mixing; (iii) forming a layer on the substrate using a centrifugation process and subsequently polymerizing it; (iv) forming the optical composite from the layer using a liquid transfer method. The technical effect is that the view field is expanded in a panoramic manner, and the level exceeding the physiological ability of human eyes is reached to the maximum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of optics, and more particularly to wearable optical devices based on optical composite materials capable of panoramically extending the field of view, and methods for preparing optical composite materials for such devices. Background Art

[0002] It is known that prior art lenses are prepared from optical materials with radial spherical refractive index gradients, such as Luneberg lenses (see Luneburg R.K., Mathematical theory of optics, Berkeley, CA: University of California Press, 1964; Roman Ilinsky, Gradient-index meniscus lens free of spherical aberration, Journal of Optics A: Pure and Applied Optics, Vol. 2, No. 5, September 2000, pp. 449-451). In addition, such lenses can be prepared using optical materials with axial or radial refractive index gradients. The main advantages of this type of lens are increased optical power, reduced aberrations and a wide field of view.

[0003] The human eye is the most obvious example of gradient optics in nature, with a lens index ranging from about 1.406 in the center of the lens to 1.386 in the less dense layers of the lens (see Hecht, Eugene; Alfred, (1987), Optics (2nd Edition), Reading, MA: Addison-Wesley. 178). This enables the human eye to obtain images with good resolution and low aberration at both short and long distances (Shirk JS, Sandrock M, Scribner D, Fleet E, Stroman R, Baer E, Hilter A, (2006), NRL Review pp. 53–61). At the same time, the field of view of the human eye is up to 120 degrees, while the field of view of clear vision (the angle range in which the human eye can recognize symbols) is approximately 30 degrees in the vertical direction and 40 degrees in the horizontal direction (Bernard C. Kress, Optical Architectures for Augmented-, Virtual-, and Mixed-Reality Headsets, SPIE Press, 2020).

[0004] It is known that various prior art methods can prepare optical materials with a refractive index gradient, such as the sol-gel method (see patent US8763430B2, cl.C03B19 / 12 published on July 1, 2014). In addition, glasses with a refractive index gradient can be prepared using neutron irradiation, chemical vapor deposition, ion exchange, ion implantation, crystal growth, glass layer superposition, etc. The main problem in preparing optical materials with a refractive index gradient is the technical complexity of the method, and the gradient range is limited by the potential refractive index of the material used.

[0005] The prior art discloses a method for preparing an optical material with a refractive index gradient, wherein the method comprises a controlled diffusion method using a component in a blank of glass, plastic or other suitable optical material suitable for producing radial and cylindrical refractive index gradients (see application US5262896A published on November 16, 1993, classification number (cl.) G02B3 / 00). The disadvantages of the prior art method are that grinding and polishing the cylindrical lens to the required precision requires labor and the refractive index gradient value is low (about 0.01-0.03) due to the limitation of the diffusion law. In addition, the transmittance of the obtained material in the visible spectrum range does not exceed 50%, and the field of view does not exceed 25-35 degrees.

[0006] The prior art discloses a method for preparing a lens with a refractive index gradient, wherein the method comprises copolymerizing two different monomers that undergo diffusion (see Wu, SP, Nihei, E., Koike, Y., Large Radial Graded-Index Polymer, Appl. Opt. 35(1), 28, 1996). Incomplete diffusion produces a composition gradient, thereby producing a refractive index gradient across the material, while two different monomers can be used and the polymer can be doped with impurities. The main disadvantages of the prior art method are the low refractive index gradient value (about 0.01-0.03) due to the limitation of the diffusion law, and the short life of the prepared material due to the migration of the doping impurities. In addition, the transmittance in the visible spectrum range does not exceed 60%, and the field of view does not exceed 25-35 degrees.

[0007] The prior art discloses a method for preparing contact lenses or intraocular lenses from an optical material with a refractive index gradient, produced by polymerizing a main polymer in a central part and then diffusing a polymer with a lower refractive index into the main polymer to produce a gradient of up to 0.4 (see patent US7857848B2, cl. G02B1 / 04 published on December 28, 2010). The disadvantages of the prior art method are poor intermediate vision, low transmission (less than 50%), visual artifacts: halos, scattering and glare, lack of accommodation and limited field of view (maximum 187 degrees) of the obtained lenses.

[0008] The prior art discloses a method for preparing a material with a refractive index gradient, in particular in the form of a large sheet, wherein the method comprises preparing a hierarchical multilayer polymer composite from a set of ordered polymer films (immiscible, miscible or partially miscible polymers) each having its own refractive index, and then forming the multilayer polymer composite sheet (see patent US7002754B2, cl. G02B3 / 00 published on February 21, 2006). The prior art method can produce a continuous, discrete or stepped refractive index gradient in the range of 0.01 to 1.0 in any axial, radial or radial spherical direction. In addition, a dynamic reversible change of the refractive index gradient can be achieved, which makes it possible to change the focal length of a lens made of the material. The disadvantages of the prior art method are the complexity of the preparation, including the need to use thermoplastic polymers, and the impossibility of preparing a material with a refractive index gradient higher than 1.0 and a transmittance higher than 50% in the visible spectrum, while achieving a field of view not exceeding 273 degrees.

[0009] The closest to the proposed invention in terms of technical essence is a wearable optical device comprising a composite material consisting of at least two layers of optically transparent polymers with nanoparticles, wherein the layers have different refractive indices (see patent US11327438B2, cl. G02B 5 / 08, G03H1 / 04 published on May 10, 2022). The document discloses a method for preparing an optical composite material, comprising the steps of preparing the nanoparticles, distributing the nanoparticles on the polymer, forming layers with different refractive indices from the optically transparent polymer with nanoparticles, forming a multilayer blank, and bonding the optical composite material together. The main disadvantage of the prior art device and method is the use of polymer nanoparticles, which leads to the formation of a relatively low refractive index gradient (about 0.2) and does not allow a sufficiently wide field of view to be obtained.

[0010] The technical problem is to eliminate the mentioned disadvantages. Summary of the invention

[0011] With respect to the device, the technical effect is to enhance its functionality, in particular to extend the field of view up to a level that exceeds the physiological capabilities of the human eye. With respect to the device, the problem has been solved and the technical effect has been achieved by a wearable optical device comprising a composite material, the composite material comprising at least two optically transparent polymer layers with nanoparticles, wherein the layers have different refractive indices, the nanoparticles are made of a high refractive material with a refractive index higher than 2.8, and the difference in the refractive index of the layers comprises not less than 0.3. The high refractive material used can be ZnO, TiO2 or ZnS. The high refractive material used can also be a van der Waals material composed of two-dimensional layers bonded together by van der Waals forces, such as but not limited to transition metal dichalcogenides, hexagonal boron nitride, graphite, MoS2, MoSe2, WS2, WSe2, SnS2, SnSe2, PtS2, PtSe2, PtTe2, ReS2, ReSe2, Cd3As2, Cd3Sb2, Cr2AlC, Cr2C, Mn2AlC, Mo2C, Mo2Ga2C, Mo3AlC2, Nb2AlC, Nb2C, Nb4AlC3, Nb4C3, Ta2C, Ta4AlC3, Ti2AlC, Ti2AlN, Ti2C, Ti2N, Ti3AlC2, Ti3C2, Ti3CN, Ti3SiC2, Ti4N3, V2Al C, V2C, V4AlC3, V4C3, PdS2, PdSe2, PdTe2, ZrS2, ZrSe2, GaSe, Sb2Te3, GaS, GaSe, Ga Te, Ca(OH)2, Mg(OH)2, MnO2, MoO3, Sb2O3, Sb2OS2, Sb2S3, Sb2Se3, Sb2Te3, As2S3, A s2Se3, As2Te3, Bi2O2Se, Bi2S3, Bi2Se3, Bi2Te3, BiSbTe3, AsP, CdI2, CdPS3, CuS, CoPS3, Cr2Ge2Te6, Cr2S3, CrBr3, CrCl3, CrGeTe3, CrPS3, CrSeBr, CuCrP2S6, CuIn7Se 11 , FeCl2, FePS3, FePSe3, GaGeTe, GaInS3, GaSeTe, GaSSe, GaPS4, GaSTe, HfSe2, HfS2, In2S3, In2Se3, InSe, InT e, InSeBr, InSnSe, MoTe2, WTe2, NbS2, NbSe2, NbSe3, VSe2, ZrSe3, MoSSe, MoWSe2, MoWS2, MoWTe2, MoNbSe2, MoO 2.5 Cl 0.5, MoReS2, MoTaSe2, MoVSe2, Na2Co2TeO6, Nb2SiTe4, NbReS2, NbReSe2, NbS3, Ni2SiTe4, Ni3TeO6, NiCl2, NiI2, NiPS3, PbI2, PbTe, ReNbS2, ReNbSe2, ReSSe, Sb2OS2, SbAsS3, SbSe, SbSi, SiP, SnPSe 3, SnS, SnSe, TaS2, TaS3, TaSe2, TaWSe2, TlSe, TiBr3, SnTe2, TiS2, TiS3, TlGaS2, TlGaSe2, TlGaTe2, TlInS2, WNbSe2, WReS2, ZrS2, ZnIn2S4, ZnPS3, ZnPSe3, ZrGeTe4, ZrS3, ZrSe2, ZrTe2 or ZrTe3. The polymer preferably has a refractive index in the range of 1.3 to 1.8, and in particular, the polymer is represented by polyvinyl alcohol, hydroxyethyl methacrylate, polydimethylsiloxane, polylactic acid, polymethyl methacrylate, polymethylpentene, polycarbonate or polyetherimide. The layers may have different refractive indices due to the nanoparticle size in one layer being larger than the nanoparticle size in another layer or due to the nanoparticle concentration in one layer being higher than the nanoparticle concentration in another layer. The polymer layers with nanoparticles are preferably stacked in such a way that the refractive index of the layers increases from one part to another of the optical composite to form a refractive index gradient. The layers can be prepared in the form of spherical elements and stacked to produce a radial spherical refractive index gradient, while the wearable optical device itself is realized in the form of a contact lens.

[0012] Regarding the method, the technical effect is that the optical composite material with a high refractive index gradient can be prepared more easily. Regarding the method, the problem has been solved and the technical effect has been achieved by a method for preparing the optical composite material, the method comprising the following steps: (i) preparing the nanoparticles, (ii) distributing the nanoparticles on the polymer, (iii) forming at least two optically transparent polymer layers with nanoparticles, wherein the layers have different refractive indices, and constructing the optical composite material from the layers obtained in step (iii), wherein in step (i), the nanoparticles are prepared from a high refractive material with a refractive index higher than 2.8 using a liquid phase femtosecond laser fragmentation or ablation method, in step (ii), the nanoparticles are distributed on the polymer by mixing so that the difference in the refractive index of at least two of the layers includes not less than 0.3, in step (iii), the polymer layer with nanoparticles is formed on a substrate using a centrifugal method and polymerized, and in step (iv) the optical composite material is formed by superimposing the layers prepared in step (iii) using a liquid transfer method. In step (ii), for different layers, the nanoparticles are mixed in different concentrations or different sizes. In step (iv), the polymer layers with different concentrations of nanoparticles prepared in step (iii) are preferably stacked in such a way that the concentration of nanoparticles in the layers increases from one part of the optical composite to another part. In step (iv), the optical composite may be formed in a fixture having a spherical inner surface. The liquid used for laser fragmentation or ablation in step (i) and the liquid used for transferring the layers in step (iv) are preferably water, alcohol or acetone. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The graphs presented show the relationship between the size of the angular field of view obtained and the difference in the refractive index of the optical composite material layers;

[0014] Figure 2 Embodiments of flat optical composites having radial refractive index gradients are presented;

[0015] Figure 3 A cross-section of an optical composite material for a proposed device in the form of a contact lens is shown, the optical composite material having layers in the form of spherical elements and having a radial spherical refractive index gradient;

[0016] Figure 4 A diagram showing naked eye image generation (120 degree field of view);

[0017] Figure 5An illustration of image generation using a wearable optical device in the form of a contact lens with a radial spherical refractive index gradient, where the lens is made of two layers (190 degree field of view);

[0018] Figure 6 Optical maps (220 degree field of view) of image generation using a wearable optical device in the form of a contact lens with a radial refractive index gradient are shown;

[0019] Figure 7 An illustration of image generation using a wearable optical device in the form of glasses with a fisheye element (325 degree field of view) is shown;

[0020] Figure 8 A process flow chart showing step (i) of preparing nanoparticles using a femtosecond laser;

[0021] Fig. 9 A schematic diagram showing step (iii) of forming a polymer layer having nanoparticles on a substrate using a centrifugation method;

[0022] Fig.10 shows a schematic diagram of forming an optical composite material from layers having different concentrations of nanoparticles in step (iv);

[0023] Fig.11 A schematic diagram of the formation of an optical composite material from layers having nanoparticles of different sizes in step (iv) is shown. DETAILED DESCRIPTION

[0024] The proposed wearable optical device uses a composite material prepared from an optically transparent polymer with a refractive index gradient. The most suitable for such applications are polymers such as polyvinyl alcohol (PVA, (C2H4O) n ), hydroxyethyl methacrylate, polydimethylsiloxane (PDMS, (C2H6OSi) n )、polylactic acid (PLA, (C3H4O2) n ), polymethyl methacrylate (PMMA, (C5H8O2) n ), polymethylpentene (PMP, (C6H 12 ) n ), polycarbonate (PC, (C 16 H 14 O3) n ) or polyetherimide (PEI, (C 37 H 24 O6N2) n ) having a refractive index in the range of 1.3 to 1.8.

[0025] Also acceptable are polymers such as polyethylene naphthalate and its isomers, such as 2,6-polyethylene naphthalate, 1,4-polyethylene naphthalate, 1,5-polyethylene naphthalate, 2,7-polyethylene naphthalate and 2,3-polyethylene naphthalate; polyalkylene terephthalates, such as polyethylene terephthalate, polybutylene terephthalate and poly-1,4-cyclohexanedimethylene terephthalate; polyimides, such as polyacrylimide; styrene polymers, such as atactic, isotactic and syndiotactic polystyrene, α-methylpolystyrene, p-methylpolystyrene; polycarbonates, such as bisphenol A-polycarbonate; poly(meth)acrylates, such as polyisobutyl methacrylate, polymethacrylic acid ester ... acrylate, polyethyl methacrylate, polymethyl methacrylate, polybutyl acrylate and polymethyl acrylate (the term "(meth)acrylate" as used herein means acrylate or methacrylate); cellulose derivatives such as ethyl cellulose, cellulose acetate, cellulose propionate, cellulose acetate butyrate and cellulose nitrate; polyalkylene polymers such as polyethylene, polypropylene, polybutylene, polyisobutylene and poly(4-methyl)pentene; fluorinated polymers such as perfluoroalkoxy resins, polytetrafluoroethylene, fluorinated copolymers of ethylene and propylene, polyvinylidene fluoride and polychlorotrifluoroethylene and copolymers thereof; chlorinated polymers such as polydichlorostyrene, polyvinylidene chloride and polyvinyl chloride; polysulfone; polyethersulfone; polyacrylonitrile; polyamide; polyvinyl acetate; polyetheramide. Also suitable are copolymers, such as styrene-acrylonitrile copolymers (preferably containing 10 to 50 wt %, preferably 20 to 40 wt % acrylonitrile), styrene and ethylene copolymers; and poly(ethylene terephthalate-1,4-cyclohexylenedimethylene terephthalate). Other polymers include bulk or grafted copolymers; acrylic rubbers; isoprene; isobutylene-isoprene; butadiene rubber; butadiene-styrene-vinylpyridine; butyl rubber; polyethylene; chloroprene; epichlorohydrin rubber; ethylene-propylene; ethylene-propylene-diene; nitrile-butadiene; polyisoprene; silicone resins; styrene-butadiene and polyurethane rubbers.

[0026] The preparation of an optical composite material from at least two layers having a refractive index difference of at least 0.3 shows an unexpected technical effect, namely enhancing the device functionality by extending the field of view up to a level exceeding the physiological capabilities of the human eye (more than 120 degrees), i.e. creating a panoramic vision. Considering the state of the art, such a high gradient can be achieved by preparing the material from two or more polymer layers 1 having different refractive indices, wherein the different refractive indices are caused by the presence of nanoparticles 2 of a high refractive material (n>2.8).

[0027] The high refractive material may be a non-layered solid having a high refractive index and high transparency in the visible light band, such as ZnO, TiO2 or ZnS. However, the most promising are van der Waals materials composed of two-dimensional layers bonded together by van der Waals forces: transition metal dichalcogenides, hexagonal boron nitride (hBN), graphite (Gr), MoS2, MoSe2, WS2, WSe2, SnS2, SnSe2, PtS2, PtSe2, PtTe2, ReS2, ReSe2, Cd3As2, Cd3Sb2, Cr2AlC, Cr2C, Mn2AlC, Mo2C, Mo2Ga2C, Mo3AlC2, Nb2AlC, Nb2C, Nb4AlC3, Nb4C3, Ta2C, Ta4AlC3, Ti2AlC, Ti2AlN, Ti2C, Ti2N, Ti3AlC2, Ti3C2, Ti3CN, Ti3SiC2, Ti4N3, V2A lC, V2C, V4AlC3, V4C3, PdS2, PdSe2, PdTe2, ZrS2, ZrSe2, GaSe, Sb2Te3, GaS, GaSe, G aTe, Ca(OH)2, Mg(OH)2, MnO2, MoO3, Sb2O3, Sb2OS2, Sb2S3, Sb2Se3, Sb2Te3, As2S3, A s2Se3, As2Te3, Bi2O2Se, Bi2S3, Bi2Se3, Bi2Te3, BiSbTe3, AsP, CdI2, CdPS3, CuS, CoPS3, Cr2Ge2Te6, Cr2S3, CrBr3, CrCl3, CrGeTe3, CrPS3, CrSeBr, CuCrP2S6, CuIn7Se 11 , FeCl2, FePS3, FePSe3, GaGeTe, GaInS3, GaSeTe, GaSSe, GaPS4, GaSTe, HfSe2, HfS2, In2S3, In2Se3, InSe, InT e, InSeBr, InSnSe, MoTe2, WTe2, NbS2, NbSe2, NbSe3, VSe2, ZrSe3, MoSSe, MoWSe2, MoWS2, MoWTe2, MoNbSe2, MoO 2.5 Cl 0.5, MoReS2, MoTaSe2, MoVSe2, Na2Co2TeO6, Nb2SiTe4, NbReS2, NbReSe2, NbS3, Ni2SiTe4, Ni3TeO6, NiCl2, NiI2, NiPS3, PbI2, PbTe, ReNbS2, ReNbSe2, ReSSe, Sb2OS2, SbAsS3, SbSe, SbSi, SiP, SnPSe 3. SnS, SnSe, TaS2, TaS3, TaSe2, TaWSe2, TlSe, TiBr3, SnTe2, TiS2, TiS3, TlGaS2, TlGaSe2, TlGa Te2, TlInS2, WNbSe2, WReS2, ZrS2, ZnIn2S4, ZnPS3, ZnPSe3, ZrGeTe4, ZrS3, ZrSe2, ZrTe2 or ZrTe3.

[0028] The layers 1 may have different refractive indices due to the average size of the nanoparticles 2 being larger in one layer than in another layer, or due to the concentration of nanoparticles 2 being higher in one layer than in another layer.

[0029] In order to form the required gradient and to extend the field of view up to a level exceeding the physiological capabilities of the human eye, two flat layers with a difference in refractive index of at least 0.3 are sufficient. However, in order to provide a clearer image and minimize aberrations, it is reasonable to form a smoother gradient and use four or more layers 1. To this end, the polymer layers 1 with nanoparticles 2 are preferably stacked in such a way that the refractive index of these layers increases from one part of the optical composite material to another part to form a refractive index gradient.

[0030] In the simplest flat embodiment, the gradient achieved will be axial [ Fig.10 ]、[ Fig.11 ]. The radial gradient can be achieved by rolling up the obtained flat multilayer polymer sheet around a rod with the maximum refractive index and then cutting it into disks.[ Figure 2 ]. To form a radial spherical refractive index gradient, layer 1 is produced in the form of spherical elements and stacked in an onion-like pattern [ Figure 3 ] - If the central element is not stacked, the optical composite material with a suitable radius of curvature can be immediately used as a ready-to-use wearable optical device in the form of a contact lens 3 [ Figure 5 ].

[0031] For example, contact lenses 3[ Figure 5 ]、[ Figure 6 ] and glasses 4[ Figure 7 ]The proposed wearable optical device in the form of is operated as follows.

[0032] In the absence of the proposed device, the retina of the unaided eye is 5[ Figure 4 ] is fully exposed to the rays 6 which, after passing through the lens 7, form an image of the objects found in the field of view. In this case, the maximum field of view is 120 degrees.

[0033] In the simplest case, the proposed wearable device represents a contact lens 3 having two polymer layers 1 with different concentrations of nanoparticles 2 [ Figure 5 ], where the layer with a higher refractive index is on the user side. In this case, a radial spherical refractive index gradient is formed, which increases the focal length of the converging rays. This results in that rays 6 outside the user's field of view under normal physiological viewing conditions also reach the retina 5 after the lens 7, and the field of view is extended to up to 190 degrees.

[0034] Similarly, the proposed device can be used in the form of glasses 4 having a flat element consisting of two layers 2 with an axial refractive index gradient [ Fig.10 ]、[ Fig.11 ].

[0035] To further extend the field of view, the proposed device is equipped with an optical composite material with a more complex gradient formed by multiple layers with smoothly varying refractive indices, which makes it possible to realize more exotic functions.

[0036] When an optical composite material having a radial refractive index gradient is used in a contact lens 3 [ Figure 6 ], ray 6 refracted in layer 1 from the outermost layer to the innermost layer is bent more strongly and forms a field of view as wide as 220 degrees.

[0037] In the case where the disclosed wearable optical device is implemented in the form of glasses 4 having a fisheye working element comprising an optical composite material having a radial refractive index gradient, in the form of a cylindrical base with hemispherical ends [ Figure 7 ], the field of view can be expanded to up to 325 degrees.

[0038] To date, the preparation of optical composite materials with the above-mentioned properties as the basic elements of the proposed wearable optical devices remains a difficult task, so the method of preparing such materials is disclosed below.

[0039] The proposed method for preparing the optical composite material comprises the following main steps.

[0040] Step (i) - Preparation of Nanoparticles

[0041] The initial step (i) involves the use of a femtosecond laser fragmentation method in a liquid such as water, alcohol or acetone [Besner, S., Kabashin, A. V., Meunier, Y., Fragmentation of colloidal nanoparticles by femtosecond laser-induced supercontinuum generation”, Appl. Phys. Let. 89 (23), 233122, 2006] or ablation method [Tselikov, GI, Ermolaev, GA, Popov, AA, Tikhonowski, GV, Panova, DA, Taradin, AS, Vyshnevyy, AA, Syuy, AV, Klimentov, SM, Novikov, SM, Evlyukhin, AB, Kabashin, AV, Arsenin, AV, Novoselov, KS, Volkov, VS, Transition metaldichalcogenide nanospheres for high-refractive-index nanophotonics and biomedical theranostics, PNAS 119 (39), e2208830119, 2022], nanoparticles 2 are prepared from high-refractive materials with a refractive index higher than 2.8. The method described is fairly simple and demonstrates good controllability of the process parameters and, most importantly, high quality of the prepared nanoparticles 2, with the degree of dispersion varying within a wide range.

[0042] As mentioned above, the most preferred class of high refractive materials is a wide range of van der Waals materials comprising two-dimensional layers held together by van der Waals forces. In this case, the selected femtosecond method of preparing nanoparticles 2 is also advantageous in that, due to the extremely short (femtosecond) duration of the method of destroying the source material and preparing the nanoparticles 2, the unique optical properties of the source material caused by its multilayer structure can be maintained.

[0043] Laser fragmentation or ablation Figure 8] is carried out using the rays 8 of a femtosecond pulsed laser, wherein the liquid is constantly stirred until the desired concentration of nanoparticles 2 is reached in the prepared solution. This results in the production of nanoparticles 2 which are passivated by OH groups and have a zeta potential in the range of -50 to -30 mV, making them soluble in the polymer without any additional functionalization (chemical treatment). In this step, the diameter of the nanoparticles 2 varies in the range of 1 to 250 nm. The separation of the nanoparticles 2 by size is accomplished using a centrifugal method [ Fig. 9 ], where the rotation speed was increased from 200 rpm to 8000 rpm, which resulted in the formation of a monodisperse solution (Robertson, JD, Rizzello, L., Avila-Olias, M., Gaitzsch, J., Contini, C., Magon, MS, Renshaw, SA, Bataglia, G., Purification of Nanoparticles by Size and Shape, Scientific Reports 6, 27494, 2016).

[0044] Step (ii) - Distributing the Nanoparticles on the Polymer

[0045] The monodisperse solution with nanoparticles 2 obtained in the previous step is then distributed on the optically transparent polymer (the specific embodiment of the polymer is described above) by mechanical mixing. For different layers 1, the nanoparticles 2 are mixed with different concentrations and / or different sizes, wherein the specific parameters of the method are defined by the required refractive index value n of the prepared layer, which is in the range of 1.3 to 3.95 for the polymer-nanoparticle mixture within the effective medium approximate limit. In order to achieve the required refractive index gradient, the difference in refractive index between at least two prepared polymer-nanoparticle mixtures must not be less than 0.3.

[0046] In order to achieve a homogeneous distribution of the nanoparticles 2 in the polymer, the prepared mixture is additionally subjected to ultrasound treatment.

[0047] Step (iii) - Forming the layer

[0048] This step includes forming at least two optically transparent polymer layers 1 having nanoparticles 2. The polymer layer having nanoparticles is formed and polymerized from droplets 10 on a rotating substrate 9 using a centrifugal method (spin coating) (Mouhamad Y., Mokarian-Tabari P., Clarke N., Jones RAL and Geoghegan M., Dynamics of polymer film formation during spin coating, Journal of Applied Physics 116, 123513, 2014) to produce a film of a predetermined thickness (in the range of 10 to 10000 nm), followed by drying [ Fig. 9 ]. The difference between the refractive indices of the layers having the largest and smallest concentration and / or size of nanoparticles 2 must be no less than 0.3.

[0049] Step (iv) - Forming the Optical Composite Material

[0050] The layers 1 with different concentrations and / or sizes of nanoparticles 2 and thus different refractive indices prepared in the previous step are stacked to form a combined multilayer optical composite using a liquid transfer method [RS Weatherup, 2D Material Membranes for Operando Atmospheric Pressure Photoelectron Spectroscopy, Topics in Catalysis 61, 2085-2102, 2018]. The liquid used to transfer the layer 1 is water, alcohol or acetone.

[0051] In the most preferred embodiment, the polymer layer 1 with the nanoparticles 2 is stacked in such a way that the concentration of the nanoparticles 2 increases from one side to the other side of the optical composite material to form a refractive index gradient in the range of 0.3 to 2.8. For this purpose, polymer layers 1 with different concentrations of [ Fig.10 ] or size[ Fig.11 ] a layer of nanoparticles 2.

[0052] The refractive index gradient can be axial and radial, or radially spherical. The axial refractive index gradient is achieved by stacking layers of polymer films with different refractive indices in the thickness direction and forming an optical composite in the form of a multilayer polymer sheet. The sheet can be rolled up and then cross-cut to prepare a disk with a radial refractive index gradient [ Figure 2]. The flat optical composite material can be used to prepare eyeglasses 4 and wearable optical devices for other applications.

[0053] To form a radial spherical gradient, particularly for use in the preparation of a wearable optical device in the form of a contact lens 3, the composite material is formed in a fixture having a spherical inner surface. In the method, the layers 1 are bent to the radius of curvature of the lens being formed and stacked one after another in an onion-like pattern [ Figure 3 ].

[0054] Industrial Applicability

[0055] The disclosed method makes it relatively easy to prepare optical composite materials with high transmittance (up to 99%) and a refractive index gradient of not less than 0.3 in the spectral region within the range of 300-800nm ​​using the latest technology. At the same time, the use of the material to prepare wearable optical devices can enhance the function of the device by extending the field of view to a level that exceeds the physiological capabilities of the human eye (from 120 degrees to at least 325 degrees).

[0056] Example

[0057] Example 1.

[0058] In order to prepare highly refractive MoS2 nanoparticles in step (i), a femtosecond laser with a pulse length of 100fs, a pulse energy of 100μJ, a wavelength of 1030nm and a repetition rate of 10kHz was used. In the fragmentation method, the source MoS2 crystal is present in deionized water, and a galvo-scanner is used to scan the crystal surface with a focused laser spot at a scanning speed of 1m / s. The radiation exposure continues until a final nanoparticle concentration of 0.1mg / ml is reached. Then, using a centrifugal method, the prepared colloidal solution is separated into 6 monodisperse solutions (distribution dispersion is less than 10%), in which the average diameters of the nanoparticles are 34, 42, 53, 65, 78 and 100nm.

[0059] In step (ii), the prepared nanoparticle solution was distributed on the polymer (polymethyl methacrylate) by mechanical mixing and subsequent ultrasonic treatment.

[0060] In step (iii), several layers in the form of 100 nm thick films are formed using a centrifugation method (spin coating), whose volume concentration of nanoparticles (selected to have a size less than 60 nm) is 0, 10, 20, 30, 40, 50, 60 and 70%, which corresponds to an effective refractive index of 1.485, 1.85, 2.2, 2.55, 2.9, 3.25, 3.6 and 3.95 for the layer at a wavelength of 750 nm.

[0061] In step (iv), the film is transferred layer by layer using a liquid transfer method and then stacked to form an optical composite material in the form of a multilayer polymer sheet, which has a refractive index gradient of 2.465 at a wavelength of 400nm. The prepared sheet is rolled into a cylinder with a radial refractive index gradient, and a fisheye optical element is cut from the cylinder, which has a flat end and a hemispherical end. The wearable optical device prepared based on this element has a transmittance of 99% and a field of view of 325 degrees.

[0062] Example 2.

[0063] In order to prepare high refractive ZnS nanoparticles with a size of 20 nm by liquid phase laser fragmentation method in step (i), a femtosecond laser with a pulse length of 100 fs, a pulse energy of 50 μJ, a wavelength of 1030 nm and a repetition rate of 10 kHz was used. In the method, ZnS microcrystals with a wurtzite crystal structure and a mass of 1 mg were immersed in a small cup filled with 5 ml of ethanol and then exposed to strong ultrasonic treatment for 5 min at a power level of 150 W. As a result, a colloidal solution of ZnS nanoparticles in ethanol with a weight concentration of 0.2 mg / ml was produced, and then the solution was subjected to a femtosecond laser fragmentation procedure. To this end, the laser irradiation with the above parameters was focused at a depth of 1 cm from the surface of the colloidal solution, while the colloidal solution itself was stirred at a speed of 300 rpm using a magnetic stirrer. Laser fragmentation within 30 minutes resulted in the production of ZnS nanoparticles with an average size of 20 nm and a volume concentration of 1*10 13 pcs / ml of colloidal solution of spherical ZnS nanoparticles.

[0064] In step (ii), the colloidal solution of the ZnS nanoparticle is mechanically mixed with polyvinyl alcohol (a kind of water-soluble thermoplastic polymer with a refractive index of 1.5 at a wavelength of 400nm) in a predetermined ratio. The mixture produced is subjected to ultrasonic stirring, and then a centrifugal method (spin coating) is used to form a 100nm thick film. Thus, a group of 100nm thick layers (polymer films) have been produced, which have a ZnS nanoparticle with various volume concentrations of 0,10,20,30,40,50,60 and 70%, and the effective refractive index of the layer under a wavelength of 400nm is 1.59,1.68,1.77,1.87,1.98,2.08 and 2.20.

[0065] In step (iv), the films were transferred layer by layer using a liquid transfer method and then stacked in a hemispherical fixture to form an optical composite material having a refractive index gradient of 0.61 at a wavelength of 400 nm. The prepared contact lens had a transmittance of 99% and a field of view of 220 degrees.

Claims

1. A wearable optical device comprising an optical composite material comprising at least two optically transparent polymer layers having nanoparticles, wherein the layers have different refractive indices, characterized in that The nanoparticles are made of a high refractive material having a refractive index higher than 2.8, and the difference in the refractive index of the layers comprises no less than 0.3, and the high refractive material is a van der Waals material consisting of two-dimensional layers bonded together by van der Waals forces.

2. The wearable optical device according to claim 1, characterized in that The van der Waals material is a transition metal dichalcogenide.

3. The wearable optical device according to claim 1, characterized in that The van der Waals material is hexagonal boron nitride, graphite, MoS2, MoSe2, WS2, WSe2, SnS2, SnSe2, PtS2, PtSe2, PtTe2, ReS2, ReSe2, Cd3As2, Cd3Sb2, Cr2AlC, Cr2C, Mn2AlC, Mo2C, Mo2Ga2C, Mo3AlC2, Nb2AlC, Nb2C, Nb4AlC3, Nb4C3, Ta2C, Ta4AlC3, Ti2AlC, Ti2AlN, Ti2C, Ti2N, Ti3AlC2, Ti3C2, Ti3CN, Ti3SiC2, Ti4N3, V2AlC, V2C, V4AlC3, V4C3, PdS2, PdSe2, PdTe2, ZrS2, ZrSe2, GaSe, Sb2Te3, GaS, GaSe, GaTe, Ca(OH)2, Mg(OH)2, MnO2, MoO3, Sb2O3, Sb2OS2, Sb2S3, Sb2Se3, Sb2Te3, As2S3, As2Se3, As2Te3 , Bi2O2Se, Bi2S3, Bi2Se3, Bi2Te3, BiSbTe3, AsP, CdI2, CdPS3, CuS, CoPS3, Cr2Ge2Te6, Cr2S3, CrBr3, CrCl3, CrGeTe3, CrPS3, CrSeBr, CuCrP2S6, CuIn7Se 11 , FeCl2, FePS3, FePSe3, GaGeTe, GaInS3, GaSeTe, GaSSe, GaPS4, GaSTe, HfSe2, HfS2, In2S3, In2Se3, InSe, InT e, InSeBr, InSnSe, MoTe2, WTe2, NbS2, NbSe2, NbSe3, VSe2, ZrSe3, MoSSe, MoWSe2, MoWS2, MoWTe2, MoNbSe2, MoO 2.5 Cl 0.5 , MoReS2, MoTaSe2, MoVSe2, Na2Co2TeO6, Nb2SiTe4, NbReS2, NbReSe2, NbS3, Ni2SiTe4, Ni3TeO6, NiCl2, NiI2, NiPS3, PbI2, PbTe, ReNbS2, ReNbSe2, ReSSe, Sb2OS2, SbAsS3, SbSe, SbSi, SiP, SnPSe3, SnS, SnSe, TaS2, TaS3, TaSe2, TaWSe2, TlSe, TiBr3, SnTe2, TiS2, TiS3, TlGaS2, TlGaSe2, TlGaTe2, TlInS2, WNbSe2, WReS2, ZrS2, ZnIn2S4, ZnPS3, ZnPSe3, ZrGeTe4, ZrS3, ZrSe2, ZrTe2 or ZrTe3.

4. The wearable optical device according to claim 1, characterized in that The refractive index of the polymer is in the range of 1.3 to 1.

8.

5. The wearable optical device according to claim 4, characterized in that The polymer is polyvinyl alcohol, hydroxyethyl methacrylate, polydimethylsiloxane, polylactic acid, polymethyl methacrylate, polymethylpentene, polycarbonate or polyetherimide.

6. The wearable optical device according to claim 1, characterized in that Since the size of the nanoparticles in one layer is larger than the size of the nanoparticles in another layer, the layers have different refractive indices.

7. The wearable optical device according to claim 1, characterized in that Since the concentration of nanoparticles in one layer is higher than the concentration of nanoparticles in another layer, the layers have different refractive indices.

8. The wearable optical device according to any one of claims 1 to 7, characterized in that The polymer layers with nanoparticles are stacked in such a way that the refractive index of the layers increases from one part to another part of the optical composite material to form a refractive index gradient.

9. The wearable optical device according to claim 8, characterized in that The layers are prepared in the form of spherical elements and stacked to produce a radial spherical refractive index gradient.

10. The wearable optical device according to claim 9, characterized in that It is used as a contact lens.

11. A method for preparing an optical composite material, the method comprising the following steps: (i) preparing nanoparticles, (ii) distributing nanoparticles on the polymer, (iii) forming at least two optically transparent polymer layers having nanoparticles, wherein the layers have different refractive indices, (iv) forming the optical composite material from the layer prepared in step (iii), Features In step (i), the nanoparticles are prepared from a high refractive material having a refractive index higher than 2.8 by using a liquid phase femtosecond laser fragmentation or ablation method. In step (ii), said nanoparticles are distributed on said polymer by mixing such that the difference in refractive index of at least two of said layers comprises not less than 0.3, In step (iii), the polymer layer having nanoparticles is formed on the substrate by a centrifugal method and polymerized, In step (iv), the optical composite material is formed by stacking the layers prepared in step (iii) using a liquid transfer method.

12. The method according to claim 11, characterized in that In step (ii), the nanoparticles are mixed at different concentrations for different layers.

13. The method according to claim 11, characterized in that In step (ii), the nanoparticles are mixed in different sizes for different layers.

14. The method according to claim 11, characterized in that In step (iv), the polymer layers having different concentrations of nanoparticles prepared in step (iii) are stacked in such a way that the concentration of nanoparticles in the layers increases from one part to another part of the optical composite material.

15. The method according to claim 11, characterized in that In step (iv), the optical composite is formed in a fixture having a spherical inner surface.

16. The method according to claim 11, characterized in that The liquid used for laser fragmentation or ablation in step (i) is water, alcohol or acetone.

17. The method according to claim 11, characterized in that The liquid used to transfer the layer in step (iv) is water, alcohol or acetone.

Citation Information

Patent Citations

  • Refractive index modulation modification in a holographic grating

    US11327438B2

  • Refractive elements with graded properties and methods of making same

    US5262896A

  • Multilayer polymer gradient index (GRIN) lenses

    US7002754B2

  • Infinite refractive index gradient (IRIG) polymers for ocular implant and contact lens applications

    US7857848B2

  • Method for manufacturing grin lens

    US8763430B2